Optimal location of car wreck adjusters. - Maltos Ortega, Luis Alberto (2016)
Problem Description: When a traffic accident occurs in cities with a large traffic flow the roads surrounding the crash site are affected by traffic congestion. In some countries, such as Mexico, even small accidents are troublesome due to the fact that a claim adjuster from the car insurance company must arrive to the site and document the accident before the vehicle may be removed as required by law. Thus, in this particular setting, the location of the adjusters becomes a key factor in providing timely service. Objectives and method of study: The propouses of this thesis is to • Provide quantitative tools for scientific support for the optimal location of car wreck adjusters. • Develop adequate mathematical models for representing some of the impor- tant company concerns. Design and develop efficient solution techniques for handling real-world instances of the problem. • Assess the quality and value of the proposed techniques based on an appropri- ate experimental design. Contributions and Conclusions: The most important contributions of this work are listed below: • With the aim of minimizing average response time, two integer programming models are introduced. • The second model make special considerations to reduce the number of vari- ables. • An scatter search heuristic was designed, built and tested over a wide set of instances with very good results.